PENGARUH PENGGUNAAN MEDIA BIG BOOK TERHADAP PEMBELAJARAN MEMBACA PERMULAAN PADA SISWA KELAS 2 SD N 02 CIBIYUK - Nikmah Sakinah; Veryliana Purnamasari; Riris Setyo Sundari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background underlying this study is the lack of early reading skills. This problem is caused by the use of learning media that are still ineffective in maximizing the development of early reading skills. The research question is: Can the Big Book medium influence improvements in the development of early reading skills among students?  This is a quantitative study in the form of a pre-experimental design using a one-group pretest-posttest design. The study population consists of all second-grade students at SD N 02 Cibiyuk for the 2025/2026 academic year. The sample consisted of 26 second-grade students selected using a saturation sampling technique, where the sample size matched the population. The results showed a pretest average of 78.65 and a posttest average of 89.42. The following data was also verified using a hypothesis test in the form of a paired t-test, which revealed a significance level (sig.) < 0.05. Therefore, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected at a significance level of α = 0.05. This indicates that the Big Book medium has a significant effect on early reading learning among students.